Frontispiece: A Happy Get‐Together – Probing Electrochemical Interfaces by Non‐Linear Vibrational Spectroscopy. Issue 55 (6th October 2022) - De, Ratnadip; Dietzek‐Ivanšić, Benjamin
Abstract : Electrochemical interfaces are key structures in energy storage and catalysis. Hence, a molecular understanding of the active sites at these interfaces, their solvation, the structure of adsorbates, and the formation of solid‐electrolyte interfaces are crucial for an in‐depth mechanistic understanding of their function. Vibrational sum‐frequency generation (VSFG) spectroscopy has emerged as an operando spectroscopic technique to monitor complex electrochemical interfaces due to its intrinsic interface sensitivity and chemical specificity. Thus, this Review discusses the happy get‐together between VSFG spectroscopy and electrochemical interfaces. For more information, see the full Review by R. De and B. Dietzek‐Ivansic (DOI: 10.1002/chem.202200407 ).